When the Common Ground Seems Shattered: Self-enclosed individualism and partial relationality in creative practice - Charalambides, Sarah (Peripeti, 2020)
Surveying different modalities and contradictions inherent to conceptions of commonality and solidarity in the arts, this article explores how cultural producers can resist essentialist configurations of political identity and practise ‘commoning’ within post-Fordist neoliberal capitalism through the notion of partial relationality.